Environmental Enrichment Expedites Acquisition and Improves Flexibility on a Temporal Sequencing Task in Mice - Rountree-Harrison, Darius; Burton, Thomas J.; Leamey, Catherine A.; Sawatari, Atomu (Frontiers in Behavioral Neuroscience, 2018)
Environmental enrichment via increased opportunities for voluntary exercise, sensory stimulation and social interaction, can enhance the function of and behaviours regulated by cognitive circuits. Little is known, however, as to how this intervention affects performance on complex tasks that engage multiple, definable learning and memory systems. Accordingly, we utilised the Olfactory Temporal Order Discrimination task which requires animals to recall and report sequence information about a series of recently encountered olfactory stimuli. This approach allowed us to compare animals raised in either enriched or standard laboratory housing conditions on a number of measures, including the acquisition of a complex discrimination task, temporal sequence recall accuracy (i.e., the ability to accurately recall a sequences of events) and acuity (i.e., the ability to resolve past events that occurred in close temporal proximity), as well as cognitive flexibility tested in the style of a rule reversal and an intra-dimensional shift. We found that enrichment accelerated the acquisition of the temporal order discrimination task, although neither accuracy nor acuity was affected at asymptotic performance levels. Further, while a subtle enhancement of overall performance was detected for both rule reversal and intra-dimensional shift versions of the task, accelerated performance recovery could only be attributed to the shift-like contingency change. These findings suggest that environmental enrichment can affect specific elements of complex, multi-faceted cognitive processes.